Differential Diagnosis of Fever of Unknown Origin in Drug Reaction with Eosinophilia and Systemic Symptom (DRESS) - Kevin Fachri Muhammad; Ferdy Ferdian; Andri Reza Rahmadi (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To describe an unusual case of drug reaction with eosinophilia and systemic symptoms presenting as fever of unknown origin (FUO) and the diagnostic hurdles that come with the presence of differential diagnosis of FUO, which is tuberculous lymphadenitis.Methods: A 34-year-old female with a chief complaint of fever that has lasted for 3 weeks accompanied with jaundice and skin rashes for 2 weeks was admitted with an indication of FUO. She had a history of carbamazepine consumption for trigerminal neuralgia 2 months prior. Cervical lymphadenopathy was palpable bilaterally and hepatomegaly, elevated liver enzyme, as well as hyperbilirubinemia were observed. After excluding differentials for many causes of prolonged fever, patient was treated for Drug Reaction with Eosinophilia and Systemic Symptom (DRESS) and was given intravenous steroid injections. Fine needle aspiration biopsy was performed for her cervical lymphadenopathy.Results: Biopsy presented a mix of sialadenitis and tuberculous lymphadenopathy. Clinical improvement was observed on the second day after steroid administration. Patient was discharged on the seventh day after steroid administration. Conclusion: FUO is one of the possible manifestations of DRESS; however, thorough investigation still needed to be done considering the possibility of more than one entity of disease that can cause FUO in patients, such as tuberculous lymphadenopathy seen in this case.